Artaxata – The capital of Artaxiad Armenia in the light of archaeological research in the eastern Lower City and Hill XIII - Gyulamiryan , Hayk A.; Lichtenberger , Achim; Muradyan , Syuzanna R.; Schreiber , Torben; Zardaryan , Mkrtich H. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The paper deals with the earliest period of the foundation of Artaxata-Artashat seen from Hill XIII in the northeastern part of the Lower City. Archaeological research since 2018 by the Armenian-German Artaxata Project has revealed the early phases of the 2nd century BC city in this area. We describe how the hill with remains of an earlier Urartian settlement was prepared for the new foundation of Artaxias-Artashes I, how a ditch was constructed and Hill XIII integrated into the fortification of the new capital city, and how a public structure was erected on the eastern summit of Hill XIII. The public structure, possibly a sanctuary, was destroyed in the early 1st century BC and in the next phase converted into a domestic area. We will discuss possible reasons why the sanctuary was not rebuilt. In the aftermath of or in the course of the destruction of Artaxata in 59 AD by Corbulo Hill XIII seems to have been abandoned and no longer been part of the Hellenistic capital. In this paper, we also discuss the possible shift in settlement in the subsequent centuries AD and consider possible reasons for this urban transformation.